Living at the Time of the End: Reading Günther Anders in the Light of the Russo-Ukrainian War - Quarta, Emmanuele (Soft Power, 2024)
The Doomsday Clock was created in 1947 by The Bulletin of the Atomic Scientists and can be defined as “a design that warns the public about how close we are to destroying our world with dangerous technologies of our own making” through the imagery of apocalypse, which is represented by midnight on the clock. Clearly, back at the dawn of the Cold war, the most recognizable threat to humanity consisted by and large of nuclear weapons, especially in the context of growing confrontation between the United States and the Soviet Union. Today, scientists at The Bulletin take into account a wider range of threats, such as climate change, new technologies, and biosecurity, when deciding whether the hands should be moved closer to – or farther from – midnight. Ever since its creation, the Doomsday Clock has been reset 24 times, the latter being in 2020, when it was moved from two minutes to midnight to 100 seconds to midnight, that is, the closest the hands had ever gotten to the hypothetical end of the world. Such decision was subsequently confirmed in January 2021, first, and then again in January 2022, roughly a month before the beginning of the Russian military invasion of Ukraine.